Ethnobotanical study of medicinal plants used for maintaining stamina in Madura ethnic, East Java, Indonesia - Akhmad Fathir; MOCH. HAIKAL; Didik Wahyudi (Society for Indonesian Biodiversity, 2021)
Abstract. Fathir A, Haikal M, Wahyudi D. 2021. Ethnobotanical study of medicinal plants used for maintaining stamina in Madura ethnic, East Java, Indonesia. Biodiversitas 22: 386-392. The use of herbal medicine that expands rapidly across the world opens a lot of opportunities for drug exploration and discovery through ethnobotanical study. Therefore, countries with high level of biological and cultural diversity like Indonesia have great opportunities to achieve this goal, and even Indonesia has its own term for a group of herbal medicine, called jamu. This research aimed to conduct ethnobotanical study of jamu used by Madura ethnic in Pamekasan District, Madura Island, Indonesia by focusing on the specific use of it for maintaining stamina. Structured interviews with purposively selected respondents of 80 knowledgeable elder women were performed to gain insights about the medicinal herb used by them. Our study found 10 recipes of jamu used by Madura ethnic for maintaining stamina. These recipes contain 19 medicinal plants belonging to 16 genera and 11 families, with the family of Zingiberaceae contributed to the largest share of species used with eight species. Turmeric (Curcuma longa) was the species with the highest use-value by the respondents and the rhizomes were the most favorable plant organ used. In conclusion, the diversity of medicinal plants used by Madura ethnic could contribute to the development of new plant-based drugs, especially those for maintaining stamina.